The effectiveness of “Mindfulness based Cognitive Therapy” on psycho-social performance of chronic low back pain patients (CLBP) - Mohammadi, Farzaneh; Imanzad, Masoomeh; Mohammadkhani, Parvaneh; Dolatshahi, Behrooz; Asghari, Mohammad ali; Tavassoli, Elahe (Advances in Nursing & Midwifery, 2014)
Abstract Background & aim: One third of people suffer from chronic pain, a condition frequently associated with decreased quality of life and high levels of psychological distress. This study was conducted to examine the effectiveness of Mindfulness Meditation for pain management on pscho-social performance of 18-65 years old women with chronic low back pain )CLBP(. Materials and method: In this Qusi experimental study, 26 volunteer female patients with CLBP referred to physical therapy, Akhavan hospital, attending a clinical assessment for treatment of chronic pain recruited using convenience sampling. Then they were randomly assigned to experimental and control groups (13 persons in each group). Both groups completed Roland and Morris Disability Questionnaire, Pain Self-efficacy Questionnaire )PSEQ( and Depression Anxiety Stress Scale)Dass-21(. The Mindfulness Meditation for pain management intervention was lasted approximately 8 weeks. The focus of this program is on awareness enhancement, attention to cognitive and emotional factors and behavioral activation finally. The control group did not receive any psychological intervention..Data was analyzed by spss-15. Finding: The result of covariance analysis indicated that the disability caused by pain significantly reduced )p=0/00( and pain self-efficacy increased in intervention group (p=0/04(. There was no statistically significant difference in depression scores between two groups (p=0/2). Conclusion: Results from the present investigation demonstrate that “Mindfulness Meditation for pain management” can enhanced the psychosocial function of patients with chronic pain by reducing the anxiety sensitivity and selective attention to pain stimuli. Keywords: Psychotherapy, Cognitive Therapy , Chronic Pain, Self-Efficacy, Performance. REFERENCES Ahn S S (2007); The effect of Korean version of Mindfulness- Based Stress Reduction program on chronic pain of workers (Dissertation). Daegu, Korea: Youngnam University. Asghari A (2012); "Methods of pain assessment", Tehran: Roshd press . (Persian) Asghari A, Mehrabian N, Paknejad M, Saed F (2010); "The psychometric properties of Depression, Anxiety and Stress Scale in chronic pain patients", Journal of Psychology and Educational Sciences . 40 42-13. (Persian). Asghari A, Najarian B, Mohamadi M, Dehghani M (2002); "Pain psychology", Tehran: Roshd press . (Persian) Asghari A, Nicholas M k (2009); "An Investigation of Pain Self-Efficacy Beliefs in Iranian Chronic Pain Patients: A Preliminary Validation of a Translated English-Language Scale", Pain Medicine . 10(4) 619-632. Asghari A, Saed F, Dibajnia P (2008); "Psychometric properties of the depression anxiety stress scales -21 (DASS-21) in non-clinical Iranian sample", International Journal of Psychology , 2(2) 82- 102. Asmundson G J G, Jacobson S J, Allerdings M D, Norton G R (1996); "Social phobia in disabled workers with chronic musculoskeletal pain", Behaviour Research and Therapy , 34(11) 939-943. Asmundson G J G, Norton P J, Norton G R (1999); "Beyond pain, The role of fear and avoidance in chronicity", Clinical Psychology Review . 19(1) 97- 119. Asmundson G J G, Norton P J, Veloso F (1999 ); "Anxiety sensitivity and fear of pain in patients with recurring headaches", Behaviour Research and Therapy . 37(8) 703 -713. Asmundson G J G, Wright K, Hadjistavropoulos H D (2005); "Hypervigilance and attentional fixedness in chronic musculoskeletal pain: consistency of findings across modified stroop and dot-probe tasks", The journal of pain, 6 (8) 497 -506. Bahyraee A (2000); "Preliminary examination of a minimal mental status examination in screening elderly patients with dementia",(Dissertation). Tehran: University of Social Welfare and Rehabilitation. (Persian).based on the practice of mindfulness meditation: theoretical considerations and preliminary results. Gen Hosp Psychiatry . 4(1) 33-47. Brown T A, Chorpita B F, Korotitsch W, Barlow D H (1997); "Psychometric properties of the depression anxiety stress scales (DASS) in clinical samples", BehaviourReaserch and Therapy , 35(1) 79- 89. Cho S, Heiby EM, McCracken LM, Lee S, Moon D (2010); "Pain-related anxiety as a mediator of the effects of mindfulness on physical and psychosocial functioning in chronic pain Patients in Korea", The Journal of Pain , 11(8) 789- 797. Craig K D (1991); Emotional aspects of pain in P.D. (ed). Edinburgh: Churchill-livingstone. Evans S, Ferrando S, Findler M, Stowell C, Smart C, Haglin D (2008); "Mindfulness- based cognitive therapy for generalized anxiety disorder", Journal of Anxiety Disorder . 22(4) 716-721. Eysenck M W (1992); Anxiety, The cognitive perspective . Hove: Erlbaum. Giesecke T, Gracely R, Williams D, Geisser M, Petzke F, Clauw D (2005); "The relationship between depression, clinical pain, and experimental pain in a chronic pain", Arthritis & Rheumatism . 52(5) 1577-1584. Greeson J M (2009); Mindfulness Research Update: 2008, Complementary Health Practice Review , 14(1) 10- 18. Hayes A M, Feldman G (2004); "Clarifying the construct of mindfulness in the context of emotion regulation and the process of change in therapy", Clin Psychol Sci Prac . 11(3) 255- 262. Kabat-Zinn, J (1982); "An outpatient program in behavioral medicine for chronic pain patients", General Hospital Psychiatry , 4(1)33-47. Kang Y S, Choi S Y, Ryu E (2009); "The effectiveness of a stress coping program based on mindfulness meditation on the stress, anxiety, and depression experienced by nursing students in Korea". Nurse Education Today . 29(5) 538-43. Kim H J (2008); "A Gestalt group pain treatment program applying mindfulness meditation and its effectiveness (Dissertation) Sungshin Women’s University": Seoul. Korea. Koenig H G (2003); "Chronic pain: biomedical and spiritual approach", The Haworth pastoral press . McCracken L M, Gauntlett-Gilbert J, Vowles K E (2007); "The role of mindfulness in a contextual cognitive-behavioral analysis of chronic pain-related suffering and disability", Pain . 131(1-2) 63-69. Melzack R, Casey K L (1968); "Sensory, motivational and central control determinants of pain: A new conceptual model, in D Kenshalo (ed): The skin Senses". Springfield , p. 137-153. Melzack R, Wall P D (1965); "Pain mechanisms: A new theory", Science .150 (3699) 971-979. Mohammadi F (2010); "The effectiveness of Mindfulness based cognitive therapy for pain management on psychosocial function in patients with chronic low back pain", (Dissertation). Tehran: University of Social Welfare and Rehabilitation. (Persian). Morone N E, Greco C M, Weiner D K (2008); "Mindfulness meditation for the treatment of chronic low back pain in older adults: A randomized controlled pilot study", Pain . 134(3) 310-319. Norton G R, Norton P J, Asmundson G J G, Thompson L A, Larsen D K (1999); "Neurotic butterflies in my stomach, The role of anxiety, anxiety sensitivity, and depression in functional gastrointestinal disorders". Journal of Psychosomatic Research . 47(3) 233- 240. Otis J D (2007); "Managing chronic pain: A cognitive-behavioral therapy approach", Oxford university press. Roland M, Morris R (1983); "A study of a natural history of the back pain, part I: development of a reliable and sensitive measure of disability in low back pain", Spine . 8 (2) 141- 148. Sanderson C A (2004); Health Psychology . United States of American: Wiley Press. Schütze R, Rees C, Preece M, Schütze M (2010); "Low mindfulness predicts pain catastrophizing in a fear- avoidance model of chronic Pain", Pain . 148 (1) 120- 127. Segal Z V, Williams J, Mark D, Teasdale J D (2002); "Mindfulness-based cognitive therapy for depression: a new approach to preventing relapse". New York: Gilford. p. 163-169. Sibinga E M, Stewart M, Magyari T, Welsh C K, Hutton N, Ellen J M (2008); "Mindfulness-based stress reduction for HIV-infected youth: a pilot study", Explore . 4 (1) 36-37. Sullivan M J, Wood L, Terry J, et al (2009); "The support, education, and research in chronic heart failure study (SEARCH): A mindfulness- based psychoeducational intervention improves depression and clinical symptoms in patients with chronic heart failure", American Heart Journal .157(1) 85-90. Turk D C, Swanson K (2007); "Efficacy and cost effectiveness treatment for chronic pain: An analysis and evidence-based synthesis. In M E Schatman, & A Campbell (Eds.) Chronic pain management: guidelines for multidisciplinary program development". New York: informa healthcare. p.15- 38. Weisenberg M (1989); Cognitive aspect of pain in Wall p and Melzck R. Textbook of pain . Williams J M G, Watts F N, MacLeod C, Mathews A (1997); Cognitive psychology and the emotional disorders . ( 2nd ed.).Chichester: Wiley. Zeidan F, Gordon N S, Merchant J, Goolkasian P (2010); "The Effects of Brief Mindfulness Meditation Training on Experimentally Induced Pain", The Journal of Pain . 11(3) 199- 209.